METHODOLOGY FOR DETERMINING THE TRIBOTECHNICAL PROPERTIES OF STRUCTURAL MATERIALS INTERACTING WITH RAW COTTON - Turaboyev, Gulomjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This paper presents a methodology for determining the tribotechnical properties of structural materials interacting with raw cotton under frictional conditions. The main objective of the study is to evaluate the frictional characteristics of materials used for the working elements of cotton-processing machinery in order to reduce mechanical damage to cotton fibers. The experiments were carried out using a disk-type tribometer under a nominal pressure of 0.04 MPa, a sliding speed of 6 m/s, and a test duration of 1 hour. Steel, aluminum, and polymer-coated samples based on ED-16 were subjected to comparative testing. The results showed that polymer coatings cause 1.5–2 times less damage to raw cotton compared to steel and aluminum surfaces. This effect is explained by the lower hardness and higher elasticity of polymer materials. The obtained results confirm that the tribotechnical properties of structural materials play a significant role in preserving the quality of raw cotton and can be effectively applied in the development of working elements for cotton-cleaning, cotton-harvesting, and textile machinery.